2009
DOI: 10.1158/1078-0432.ccr-07-5261
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hepatocellular Carcinoma Using Glycomic Analysis

Abstract: Purpose: Hepatocellular carcinoma (HCC) represents an increasing health problem in the UnitedStates. Serum a-fetoprotein, the currently used clinical marker, is elevated in only f60% of HCC patients; therefore, the identification of additional markers is expected to have significant public health impact.The objective of our study was to quantitatively assess N-glycans originating from serum glycoproteins as alternative markers for the detection of HCC. Experimental Design: We used matrix-assisted laser desorpt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 131 publications
(162 citation statements)
references
References 37 publications
7
153
1
1
Order By: Relevance
“…N-Glycans were detached with PNGaseF (New England Biolabs) overnight at 37°C, reduced with ammonium-borane complex (Sigma-Aldrich), and permethylated as described previously (9,32). MALDI-TOF MS/MS spectra were acquired on a 4800 mass analyzer (AB Sciex) equipped with an Nd:YAG 355-nm laser.…”
Section: Methodsmentioning
confidence: 99%
“…N-Glycans were detached with PNGaseF (New England Biolabs) overnight at 37°C, reduced with ammonium-borane complex (Sigma-Aldrich), and permethylated as described previously (9,32). MALDI-TOF MS/MS spectra were acquired on a 4800 mass analyzer (AB Sciex) equipped with an Nd:YAG 355-nm laser.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps the most widely used profiling methods are normal phase HPLC of fluorescently labeled glycans (14,15) and MALDI/TOF mass spectrometric screening of permethylated glycans (16). Chromatographic resolution of the fluorescently labeled complex glycan mixtures can be somewhat limited, although MALDI/TOF screening has lower quantitative accuracy, but both methods have provided good evidence for quantitative shifts in the distribution of protein-associated N-glycans in cancer diseases (17,18). Optimized LC-MS/MS analysis of glycans and even glycopeptides allows improved resolution of isomers and further supports the presence of disease-related protein glycoforms that could impact protein function and disease progression (19 -21).…”
mentioning
confidence: 99%
“…Serum glycomic studies to discover novel glycan cancer biomarkers have been highlighted (Adamczyk et al 2012 ). Numerous glycan tumor marker candidates for various cancers, including liver (Kaji et al 2013 ;Kamiyama et al 2013 ;Wu et al 2012 ;Tang et al 2010 ;Goldman et al 2009 ;Comunale et al 2009 ;Tanabe et al 2008 ;Ressom et al 2008 ), ovary (Biskup et al 2013 ;Hua et al 2013 ;Alley et al 2012 ;Abbott et al 2010 ;Leiserowitz et al 2008 ), pancreas (Li et al 2009 ;Okuyama et al 2006), breast (de Leoz et al 2011Alley et al 2010 ;Zeng et al 2010 ;Storr et al 2008 ;Abd Hamid et al 2008 ;Kyselova et al 2008 ;Kirmiz et al 2007 ), prostate , lung (Arnold et al 2011 ), colorectum (Zhao et al 2012 ), bile duct (Silsirivanit et al 2011 ), and esophagus ) cancers, have been reported. Most of these glycomic analyses have been carried out by newly developed high-throughput platform technologies, such as mass spectrometry-based methods and lectin-based methods, which have enabled the effi cient analysis of large cohorts of samples.…”
Section: Glycomic Studies On Serum Of Cancer Patientsmentioning
confidence: 99%